The effect of pregerminative treatments on the emergence of Guaiacum sanctum L. (Zygophyllaceae) seedling - Mex Villalobos, María Margarita; Carballo Hernández, José Ignacio; González Lazo, Edith; Uribe San Miguel, Julian Alberto; Dzib Castillo, Benito Bernardo (Acta Universitaria, 2022)
In Mexico, there is the guayacán species (Guaiacum sanctum L.) which is registered as a threatened species within the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), group II. A problem for their reproduction from seeds is that it requires pregerminative treatments when they are not sown after harvest, since they may present physiological dormancy and a decrease in its viability. Consequently, the objective of the present work was to identify the emergence of seedlings from seed scarification. The treatments were six, with four repetitions; the experimental design was randomized. Statistical analyzes were performed using a T test with INFOSTAT software. The results showed that there are statistical differences (p < 0.0001) between treatments. It is concluded that the best scarification treatments were soaking seeds in water for 24 hours and immersing seeds in hydrogen peroxide diluted in water (3 ml L-1) for 15 minutes.